Experiences of cancer immunotherapy with immune checkpoint inhibitors (ExCIm)—insights of people affected by cancer and healthcare professionals: a qualitative study protocol. Issue 5 (27th May 2021) - Jennings, Stephen; Anstey, Sally; Bower, Janet; Brewster, Alison; Buckman, John; Fenlon, Deborah; Fitzsimmons, Deborah; Watts, Tessa
Abstract : Introduction: There is a global interest in cancer immunotherapy. Clinical trials have found that one group, immune checkpoint inhibitors (ICIs), has demonstrated clinical benefits across various cancers. However, research focused on the experiences of people affected by cancer who have undergone this treatment using qualitative methodology is currently limited. Moreover, little is known about the experiences and education needs of the healthcare staff supporting the people receiving these immunotherapies. This study therefore seeks to explore the experiences of using ICIs by both the people affected by cancer and the healthcare professionals who support those people, and use the findings to make recommendations for ICI supportive care guidance development, cancer immunotherapy education materials for healthcare professionals, cancer policy and further research. Methods and analysis: Patient participants (n = up to 30) will be recruited within the UK. The sample will incorporate a range of perspectives, sociodemographic factors, diagnoses and ICI treatments, yet share some common experiences. Healthcare professionals (n = up to 15) involved in supporting people receiving immunotherapy will also be recruited from across the UK. Data will be generated through in-depth, semistructured interviews. Reflexive thematic analysis will be used to obtain thorough understanding of individual's perspectives on, and experiences of, immunotherapy. Study dates are as follows: December 2019–March 2022. Ethics and dissemination: The research will be performed in accordance with the UK Policy for Health and Social Care Research and Cardiff University's Research Integrity and Governance Code of Practice (2018). The study received ethical approval from the West Midlands and Black Country Research Ethics Committee in October 2019. Health Research Authority and Health and Care Research Wales approvals were confirmed in December 2019. All participants will provide informed consent. Findings will be published in peer-reviewed journals, non-academic platforms, the Macmillan Cancer Support website, disseminated at relevant national and international conferences and presented via a webinar. The study is listed on the National Institute for Health Research (NIHR) Clinical Research Network Central Portfolio.